The Wealth of Fish Species at Fish Auction Houses (TPI) in Rembang Regency as a Biology Learning Resource in High School - Purwaningsih, Astuti; Alimah, Siti (Journal of Biology Education, 2021)
Rembang is famous for the marine products as one of the main commodities. This is inseparable from the large number of Fish Auction Houses (TPI) in several sub-districts located on the north coast of Rembang that contribute marine products to support the economic sector in Rembang Regency. TPI is a market where fishermen can land the fish they get and serve as a place to sell them and various other marine products. The Species of Fish in TPI Rembang Regency have a potential to be used as a learning resource in the form of an encyclopedia, and a function as a learning supplement. The method of the study was modified research and development (R&D) of Borg & Gall (2003). The encyclopedia's feasibility level validation refers to the modified BSNP 2014 standard of teaching material feasibility, which includes four components of feasibility, namely content, language, presentation, and graphics. Validity and feasibility test of the encyclopedia was carried out by students using a gaps test to measure the readability and the questionnaire responses of students to the encyclopedia. The percentage of feasibility the encyclopedia by biology experts and teacher reached 90.23% with very feasible criteria. The percentage of readability of the encyclopedia through the gap test reached 98.22% with high level criteria. The percentage of students' responses to the encyclopedia through questionnaires reached 88.9%. The high readability level and very feasible criteria resulting from this study indicate that the encyclopedia developed is feasible for use as a source of high school biology learning.